Laparoscopic choledochal cyst resection using a novel articulating instrument in pediatric patients - Nathan S. Rubalcava; Richard E. Overman; Mercedes Pilkington; Christa N. Grant; James D. Geiger; Marcus D. Jarboe; K. Elizabeth Speck (Journal of Pediatric Surgery Case Reports, 2021)
Background: Historically, choledochal cyst excision has been performed as an open procedure. Controversy remains regarding managing this technically challenging entity in a minimally invasive fashion. Methods: A novel mechanically-designed intuitive, articulating instrument is used to facilitate intracorporeal suturing when there is limited working space. The mechanical design of the three-axis Gimbal cuff facilitates intracorporeal suturing by providing intuitive wristed function to the surgeon by translating the surgeon's wrist movement to the end effector. Results: We describe the adoption of a novel articulating instrument to facilitate a primary hepaticoduodenostomy within the limited space of a pediatric porta and a redo hepaticojejunostomy. Conclusions: These cases demonstrate the use of a novel articulating needle driver to sew an intracorporeal bilio-enteric anastomosis which obviates the need for robotic technology while expanding a laparoscopic surgeon's armamentarium.